Total Synthesis of Bis-anthraquinone Antibiotic BE-43472B - Yamashita, Yu; Hirano, Yoichi; Takada, Akiomi; Takikawa, Hiroshi; Suzuki, Keisuke (Synthesis, 2018)
This is a full account of our synthetic endeavor on the total synthesis of bis-anthraquinone antibiotic BE-43472B, an unusual octacyclic aromatic polyketide with a bis-anthraquinone scaffold. Three key steps enabled a facile access to the anthraquinone unit corresponding to the ABCF rings; (1) cyclo-condensation or -addition of benzonitrile oxides with cyclic enone derivatives, (2) benzoin cyclization for the stereoselective ring fusion with an angular hydroxy group, and (3) pinacol rearrangement for stereoselective installation of the angular aryl group. Other keys for the success include, (4) diastereoselective methylation of a lactol derivative, and (5) late-stage installation of the C3 hydroxy group through stereoselective oxirane ring formation via halohydrin derivatives. Whereas oxidation of the double bond in the enone with an adjacent 1,3-diketone moiety failed, the projected oxidation was achieved with the alkene keeping the isoxazole moiety intact as a 1,3-diketone equivalent. In the racemic total synthesis, X-ray crystal structure analysis of the target was achieved, proving the three-dimensional architecture for the first time. The asymmetric total synthesis was also achieved by exploiting a cycloadduct of the nitrile oxide and the enantiomerically pure cyclohexenone, which was convertible to the common intermediate via dehydrogenation followed by alkoxycarbonylation.
Keywords: antibiotics; bis-anthraquinone; isoxazole; natural products; total synthesis